1990
DOI: 10.1037/0096-3445.119.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a problem-solving skill: Levels of organization and use of working memory.

Abstract: We examined the acquisition of a problem-solving skill at three levels of organization-strategy, subgoal, and operator-and investigated changes in temporary storage, manipulation of information, and coordination of multiple representations. 6 college students practiced minimizing the simulated cost of solving diagnostic problems with digital electronic circuits for approximately SO hr (347 problems). Ss were tested on declarative knowledge, inferential skills at the subgoal level, and ability to solve problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…This is certainly true for the present endeavor. For example, while there are some examples of the effectiveness of increased CI during training outside the traditional purview of motor skill acquisition (Carlson, Khoo, Yaure, & Schneider, 1990;, it is hard to ignore that the vast majority of studies addressing CI have focused on skill acquisition in the motor domain. Motor learning is intentionally the domain of interest in the present work.…”
Section: Scope and Limitations Of The Reviewmentioning
confidence: 99%
“…This is certainly true for the present endeavor. For example, while there are some examples of the effectiveness of increased CI during training outside the traditional purview of motor skill acquisition (Carlson, Khoo, Yaure, & Schneider, 1990;, it is hard to ignore that the vast majority of studies addressing CI have focused on skill acquisition in the motor domain. Motor learning is intentionally the domain of interest in the present work.…”
Section: Scope and Limitations Of The Reviewmentioning
confidence: 99%
“…Gopher, Brickner, & Navon, 1982), (4) incidental learning of sequential structure (see, e.g., Cohen et al, 1990), and (5) speedup ofcomponent problem-solving processes (see, e.g. Carlson et al, 1990), among other things, In general, the benefits of practice have been found to be relatively specific to the items practiced and the conditions under which they were practiced (see, e.g., Healy & Bourne, 1995;Logan, 1990) but not to the physical responses that were made (see, e.g., Cohen et al, 1990; We thank Peter Dixon, Gordon Logan, and John Wixted for helpful comments on an earlier version of this paper. Correspondence concerning this article should be sent to R. W. Proctor, Department of Psychological Sciences, Purdue University, West Lafayette, IN 47907-1364 (e-mail: proctor@psych.purdue.edu).…”
mentioning
confidence: 99%
“…Shiffrin & Schneider, 1977), lexical decision (e.g, Logan, 1990), problem solving (e.g., Carlson, Khoo, Yaure, & Schneider, 1990), and sequence learning (e.g., Cohen, Ivry, & Keele, 1990). In different tasks, practice has been shown to promote (l) perceptual unitization of features and forms (see, e.g., Pellegrino, Doane, Fischer, & Alderton, 1991), (2) strengthening of stimulus-tointerpretation associations (e.g., associations of stimuli to word and nonword categories in lexical decision tasks; Logan, 1990), (3) development oftime-sharing skill (see, e.g.…”
mentioning
confidence: 99%
“…This kind of analysis is a priori and presents several difficulties. It is, at the moment, out of the question to find a formal language Carlson et al 1990) No Yes to describe all problem-solving that is complete (that is that enables researchers to describe every possible problem-solving task). It is thought that holistic approaches to complexity have a better chance of success, in that they do not need to decompose tasks into sub-components and the authors have oriented their efforts in this direction (see Quesada et al 2001Quesada et al , 2002.…”
Section: Discussionmentioning
confidence: 99%